Penerapan Metode Kooperatif tipe Jigsaw dengan menggunakan Strategi Active Learning terhadap Mata Pelajaran Pendidikan Agama Islam - Andianita Eka Mahfutri; Eni Fariyatul Fahyuni (Universitas Batanghari Jambi, 2023)
The learning methodology used is a modification of the learning process of Islamic Religious Education. The way people learn now is the standard. Although it has not kept pace with the evolution of the site, teachers continue to use it extensively in limited circumstances. As a person, the teacher who is solely responsible for the quality of education must be encouraged by sufficient capacity and knowledge. The teacher must provide learning methods that are suitable for the ongoing learning process. The background of this research is that learning is an interaction between students and educators when participating in the learning process of Islamic Religious Education lessons. As a result, teachers must use the most effective teaching techniques for each study, one of which is by utilizing a learning approach from the results of classroom action research. This research is a classroom action research on the application of the jigsaw type cooperative method using an active learning strategy for Islamic Religious Education lessons. Evaluating the application of the jigsaw cooperative method using an active learning strategy for Islamic Religious Education subjects. The research results obtained in the application of this method show that there is an increase in positive things and leads to better things, such as learning activities in class and student discussions between students and students between teachers, as well as fostering activeness in implementing the learning process in Islamic Religious Education subjects.